The Influence of Work Motivation, Work Stress, and Work Environment on The Performance of State Civil Apparatus in the Office of The Regional Revenue Agency (UPTD) South of Malang, Province of East Java - Naim, Naim; Helmita, Helmita (International Journal of Business, Law, and Education, 2024)
Human resources are the science and art of regulating the relationship and role of the workforce to be effective and efficient, helping the realization of company, employee, and community goals, apart from human resources, work motivation and stress can also contribute to ASN performance, the objectives of this research include; to determine the effect of motivation, work stress and work environment together on employee performance at the Regional Revenue Agency Office of the Technical Implementation Unit for Regional Revenue Management in South Malang, East Java Province, either simultaneously or partially. Methods of data collection are done by the method of questionnaires and documentation. Validity test with Product moment technique, Alpha Crombach reliability test. Hypothesis testing using t-test and F-test. The results in this study are 1) there is an effect of motivation, work stress, and work environment together on employee performance in South Malang, Java province, (2) there is a significant influence on motivation on employee performance in South Malang, East Java Province, (3) there is a significant effect of work stress on employee performance in Southern Malang, East Java Province, and (4) there is a significant effect of work environment on employee performance in Southern Malang, East Java Province